Tomada de decisão e habilidades sociais de crianças com transtorno de déficit de atenção/hiperatividade - Daniel Foschetti Gontijo (2013)
Introduction: The literature shows that, compared to typically developing children, children with ADHD tend to prefer immediate rewards than delayedeven if the latter are largerand make riskier choices. As a result, it is said that they have a higher "temporal discounting" and abnormal sensitivity to reinforcement and punishment in the context of decision making. Moreover, children with ADHD are more likely to show deficits in social skills. Objectives: To investigate whether measures of decision making correlate with measures of social skills, and if clinical and comparison groups differ on these measures. Method: Thirty-three children with ADHD (8-11 years) and 33 typically developing children (8-11 years) underwent two decision-making computerized tests and the Social Skills Rating System (SSRS-BR). Their parents also completed a version of the SSRSBR. In Maudsley's Index of Childhood Delay Aversion (MIDA), participants must choose between waiting 2 seconds to destroy a spaceship and earn one point, or to wait 30 seconds to destroy two spacecraft and earn two points. The preference for the choice of one point indicates higher temporal discounting and presumably greater delay aversion. In Hungry Donkey Task (HDT), the participants must continually choose between four ports (A, B, C and D) whose rewards and penalties (gains and losses of apples, respectively) vary in frequency and magnitude. An index of sensitivity to profits and losses and an index of sensitivity to the magnitude and frequency of penalties were calculated to do the main analyzes. Results: Children with ADHD had worse ratings in most social skills. There were no group differences in performance of MIDA and on key measures of HDT. The preference for the choices of two points in MIDA correlated with global social skills and self-control/civility and passive self-control classes. Some measures of HDT correlated with overall social skills and assertiveness, self-control, avoidance of problems and cooperation classes. Conclusion: The main measures of MIDA and HDT did not correlate with measures of social skills. The scheme of continuous reinforcement in MIDA and the complexity of the schemes of HDT may have produced choice profiles somewhat similar to those that arise in natural contexts. Nevertheless, the correlations found suggest that social skills are related to the sensitivity of children to the delay, the frequency and magnitude of the consequences of their choices.